2012
DOI: 10.1016/j.ajpath.2012.06.033
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptic Accumulation of Hyperphosphorylated Tau Oligomers in Alzheimer Disease Is Associated With Dysfunction of the Ubiquitin-Proteasome System

Abstract: In Alzheimer disease (AD), deposition of neurofibrillary tangles and loss of synapses in the neocortex and limbic system each correlate strongly with cognitive impairment. Tangles are composed of misfolded hyperphosphorylated tau proteins; however, the link between tau abnormalities and synaptic dysfunction remains unclear. We examined the location of tau in control and AD cortices using biochemical and morphologic methods. We found that, in addition to its well-described axonal localization, normal tau is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
371
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 390 publications
(408 citation statements)
references
References 47 publications
21
371
0
1
Order By: Relevance
“…2 C and D) (20). Analysis of the LTP data revealed a significant CUS × Genotype interaction [F (1,27) = 6.283, P = 0.018] and overall effects of CUS [F (1,27) = 11.24, P = 0.002] and Genotype [F (1,27) = 41.35, P < 0.0001]. In addition, post hoc analysis revealed that LTP was reduced in slices from CUS-treated WT (P = 0.002), but not CUS-treated Tau-KO (P = 0.92), mice compared with their controls.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…2 C and D) (20). Analysis of the LTP data revealed a significant CUS × Genotype interaction [F (1,27) = 6.283, P = 0.018] and overall effects of CUS [F (1,27) = 11.24, P = 0.002] and Genotype [F (1,27) = 41.35, P < 0.0001]. In addition, post hoc analysis revealed that LTP was reduced in slices from CUS-treated WT (P = 0.002), but not CUS-treated Tau-KO (P = 0.92), mice compared with their controls.…”
Section: Significancementioning
confidence: 99%
“…Tau hyperphosphorylation and missorting in dendrites and synapses are considered key mechanisms in the neuronal damage and atrophy that characterize AD (24)(25)(26)(27). In light of the above evidence that Tau is required for the manifestation of CUS-induced neuronal atrophy and dysfunction (Figs.…”
Section: Chronic Stress Evokes Tau Hyperphosphorylation and Missortinmentioning
confidence: 99%
See 1 more Smart Citation
“…New findings on the role of tau protein have been described by Tai et al [23], who demonstrated that, in addition to its well-described axonal localization, tau is present at both presynaptic and postsynaptic terminals in normal human brains. In AD, tau becomes hyperphosphorylated and misfolded at both terminals, and the accumulation of hyperphosphorylated oligomers at synapses is associated with increased ubiquitinated substrates and increased proteasome components, consistent with dysfunction of the ubiquitin-proteasome system.…”
Section: Research Aspectsmentioning
confidence: 98%
“…Thus, synaptic accumulation of hyperphosphorylated tau was observed in cells with a defective ubiquitin/proteasome system [53]. Since ubiquitinated tau is mainly found in the insoluble NFTs which accumulate late in AD rather than in the soluble oligomers, ubiquitination may be a way of detoxification.…”
Section: Posttranslational Modifications Influencing Tau Toxicitymentioning
confidence: 98%